3D nest-shaped Sb2O3/RGO composite based high-performance lithium-ion batteries. Issue 39 (27th September 2016) - Zhou, Jing; Zheng, Caihong; Wang, Hua; Yang, Jie; Hu, Pengfei; Guo, Lin
Abstract : A Sb2 O3 /graphene composite with nest-shaped architecture has been prepared, and exhibits superior electrochemical performance as an anode material in lithium-ion batteries. Abstract : A Sb2 O3 /graphene composite with nest-shaped architecture has been successfully prepared. Compared with pure Sb2 O3 materials, the Sb2 O3 /graphene composite exhibits superior electrochemical performance as an anode material in lithium-ion batteries, and this should be attributed to the synergistic effects of the high conductivity of graphene and the novel nest-shaped structure of the composite.